2017
DOI: 10.1002/bem.22048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adverse environmental conditions and protective clothing on temperature rise in a human body exposed to radiofrequency electromagnetic fields

Abstract: This study considers the computationally determined thermal profile of a finely discretized, heterogeneous human body model, simulating a radiofrequency electromagnetic field (RF-EMF) worker wearing protective clothing subject to RF-EMF exposure, and subject to various environmental conditions including high ambient temperature and high humidity, with full thermoregulatory mechanisms in place. How the human body responds in various scenarios was investigated, and the information was used to consider safety lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Limits on whole-body exposure are designed to take into account the total heat load on the human body from exposure at these frequencies. Only two studies considered here have reported changes in core body temperature from whole body exposures, and only up to 6 GHz (Hirata et al, 2013;Moore et al, 2017).…”
Section: Whole-body Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Limits on whole-body exposure are designed to take into account the total heat load on the human body from exposure at these frequencies. Only two studies considered here have reported changes in core body temperature from whole body exposures, and only up to 6 GHz (Hirata et al, 2013;Moore et al, 2017).…”
Section: Whole-body Exposuresmentioning
confidence: 99%
“…As in comments in section 5.3, most of the computational studies reported here assume an ambient (or environmental) temperature of around 22 °C-28 °C (room temperature). In a modeling study, Moore et al (2017) investigated the effects of exposure to RF energy in environments with elevated temperatures and high relative humidity, considering situations where heavy protective clothing must be worn. One scenario assumed exposure to RF energy at 6 GHz in an environment with ambient temperature of 38 °C and relative humidity of 60% (nearly an intolerable environment, with a 'heat index' value on the threshold of 'extreme danger').…”
Section: Whole-body Exposuresmentioning
confidence: 99%
“…No previous studies evaluated the temperature elevation in human head models for local exposure while considering thermoregulation. It should be noted that several studies computed the temperature elevation for whole-body exposures [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current situation, the rationale for exposure limits and guidance relies on the Adair and Berglund model. This can be done with quite some confidence, since more recent and more detailed RF exposure modeling studies have confirmed their thermal predictions [32][33][34][35][36][37]. Children have a 4 Concepts in Magnetic Resonance Part B Less than 10% of the examinations is performed with SA > 3 kJ/kg.…”
Section: Core Temperature Predictionsmentioning
confidence: 92%